Butterflies. Issue 4 (2nd October 2017) - Sakhat, Zaza
ABSTRACT: This essay illustrates group work with adolescent girls struggling with emotional dysregulation and maladaptive coping. Mutual aid and female empowerment are advanced through the development of interpersonal relationships and interaction related to stress management, adaptive coping strategies, diversity, healthy relationships, self-esteem, self-harm and emotional regulation.